Sistem Sosial dan Kebudayaan Islam Masyarakat Donggo Ditengah Pluralisme Agama - Anwar, Anwar; Subari, Subari (Lembaga Penelitian dan Pendidikan Mandala, 2023)
In a society that is predominantly Muslim, Donggo is a model of diversity because there are various monotheistic religions and different cultures that have developed in the region. This research aims to determine the social and cultural practices and systems of Islamic society in Donggo by using descriptive qualitative research which emphasizes the interview approach as the main basis for data collection. The methods include deductive and inductive methods as a comparison material, and then conclusions can be drawn. The research results show that the social system of the Donggo community is built on the basis of joint deliberation in the development of Islamic culture, both physical development and massive Islamic preaching carried out in the area. The Islamic social and cultural principles of the Donggo community amidst multiculture are carried out together to resolve existing problems.